2008
DOI: 10.1111/j.1471-4159.2008.05406.x
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐synuclein aggregation and cell death triggered by energy deprivation and dopamine overload are counteracted by D2/D3 receptor activation

Abstract: Progressive degeneration and intraneuronal Lewy bodies made of filamentous a-synuclein (a-syn) in dopaminergic cells of the nigrostriatal system are characteristics of Parkinson's disease (PD). Glucose uptake is reduced in some of the brain regions affected by PD neurodegenerative changes. Defects in mitochondrial activity in the substantia nigra have been observed in the brain of patients affected by PD and substantia nigra lesions can induce the onset of a secondary parkinsonism. Thus, energy starvation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
105
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 77 publications
(118 citation statements)
references
References 41 publications
13
105
0
Order By: Relevance
“…We have previously shown that glucose deprivation, which mimics decreasing energy supply in the ageing brain, induces the formation of α-syn insoluble aggregates, decreases dopamine cell viability and alters their function (Bellucci et al, 2008(Bellucci et al, , 2011a. In addition, we have shown that glucose deprivation is also able to induce α-syn aggregation within the endoplasmic reticulum (ER).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…We have previously shown that glucose deprivation, which mimics decreasing energy supply in the ageing brain, induces the formation of α-syn insoluble aggregates, decreases dopamine cell viability and alters their function (Bellucci et al, 2008(Bellucci et al, , 2011a. In addition, we have shown that glucose deprivation is also able to induce α-syn aggregation within the endoplasmic reticulum (ER).…”
Section: Discussionmentioning
confidence: 98%
“…S1E-G; Bellucci et al, 2008Bellucci et al, , 2011a. Indeed, urea-soluble α-syn aggregates (Bellucci et al, 2008) and thioflavin-S-positive α-syn inclusions (supplementary material Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations